The Influence of Leader-Member Exchange and Talent Management on Employee Performance with Employee Engagement and Employee Commitment as Mediation Variables in Construction Company Employees - Mochamad Ramli Nur Hasan; Budi Widjaja Soetjipto (Green Publisher Indonesia, 2025)
Employee performance refers to the extent to which employees are able to achieve job goals and meet the standards set by the company. Leader-member exchange is a theory that explains the quality of interpersonal relationships between leaders and subordinates, which can influence motivation and employee performance. Talent management is a strategy for managing organizational talent, involving the recruitment, development, and retention of talented employees to ensure they contribute maximally. Employee engagement refers to the level of emotional involvement and commitment employees have towards their work, which directly impacts productivity and employee performance. Meanwhile, employee commitment reflects the loyalty of employees to the organization and their desire to continue contributing in the long term. This study was conducted with 235 employees of PT Adhi Karya (Persero) Tbk, using data collected through a questionnaire survey. The results of the study show that leader-member exchange and talent management have a positive effect on employee performance, with employee engagement acting as a significant mediator. However, employee commitment does not play a mediating role in this relationship. This study confirms the importance of strong interpersonal relationships between leaders and subordinates, as well as effective talent management, in enhancing employee performance.